Energia da água: comunidades rurais e sistemas de abastecimento na Chapada das Veredas, Alto Jequitinhonha - Erick José de Paula Simão (2021)
Water scarcity has become a central issue for societies since the mid-twentieth century. The problems arising from the lack of the resource fall mainly on rural populations. Farming families perceive water as a common good, a gift with multiple uses. For these families, water is linked to maintaining life, producing food, quench animals and generating income. In Alto Jequitinhonha, Minas Gerais, developmental projects supported by the military government in the mid-1970s culminated in the implementation of eucalyptus monocultures in the plateaus. This process brought environmental and socioeconomic damages that fell on the farming families. Farming communities were deprived of access to common land, natural resources and, above all, access to springs. The main objective of this study was to investigate the demand for energy to provide water in communities and rural establishments of family farming affected by eucalyptus monoculture. The research was carried out in six rural communities around the Chapada das Veredas, whose water sources were affected by eucalyptus monoculture. Guided by expert farmers, the researchers visited the locations to recognize the field; community members built cartographic sketches that referred to the spatial organization and agro-environments; Interviews were carried out with 57 families from the six communities, with expert community farmers, with Turmalina's secretary of agriculture and companies providing energy and water supply services. It was noted that the communities sought to mitigate the scarcity situation by spatially reorganizing themselves, demanding public policies and socially constructed forms of supply. They thus articulated supply systems, but need to deal with the challenge of new dependency relationships to have access to water: energy, public policy, monetary resources and political mediation.